2010
DOI: 10.1345/aph.1m469
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Fistula Associated with Sunitinib in a Patient Previously Treated with Radiation Therapy

Abstract: This is a rare case of a bronchial perforation leading to a fistula associated with sunitinib treatment after mediastinal radiation therapy. Clinicians may consider strict follow-up of patients with proximal lung metastases treated with sunitinib (CT scan and, if appropriate, placement of an endobronchial stent).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Furthermore, all three patients had previously been treated with external beam irradiation of the neck. As some authors have reported an association between TK‐inhibitors and fatal bleeding events in patients subjected to radiotherapy, we may hypothesize that previous radiotherapy may represent a concomitant condition contributing to the occurrence of fatal haemorrhage. To prevent bleeding complications, we suggest excluding patients with mucosal damage related to neoplastic infiltration and those with previous haemorrhages.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, all three patients had previously been treated with external beam irradiation of the neck. As some authors have reported an association between TK‐inhibitors and fatal bleeding events in patients subjected to radiotherapy, we may hypothesize that previous radiotherapy may represent a concomitant condition contributing to the occurrence of fatal haemorrhage. To prevent bleeding complications, we suggest excluding patients with mucosal damage related to neoplastic infiltration and those with previous haemorrhages.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, a study of 43 head and neck cancer patients treated with bevacizumab and chemoradiotherapy identified five patients who formed an aerodigestive fistula with treatment (22). Bronchial fistula formation after treatment with sunitinib and radiation therapy for a pulmonary renal cell metastasis has also been reported (23). A history of esophagitis, radiation therapy at the fistula formation site, or instrumentation was common to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a report of lethal small bowel perforation after radiation for lumbar metastasis during sorafenib administration; moreover, the case of a lethal bronchial fistula that occurred after radiation for mediastinum lymph node metastasis during sunitinib therapy was published [9,10]. The current knowledge about the combination of tyrosine kinase inhibitors with radiation therapy has been reviewed by Niyazi et al .…”
Section: Discussionmentioning
confidence: 99%